Temperament structures and the effectiveness of individual play in football - Bojkowski, Łukasz; Tomczak, Maciej (Frontiers in Psychology, 2024)
Background: Regulatory Theory of Temperament distinguishes two traits involving the time course of responses and four relating to how energy is distributed and stored. This theory enables the presentation of entire structures of temperament traits and it is relevant for assessing an individual's ability to process stimulation and influence their performance during competitions. In our cross-sectional the present study, these structures are examined in relation to the offensive, defensive, and comprehensive effectiveness of an individual player's actions.The study included 91 football players aged between 20 and 31 years, who had approximately 10 years of training experience. The Formal Characteristics of Behaviour -Temperament Inventory was utilised to assess temperamental traits, while a simulation game was employed to evaluate the effectiveness of each individual player's actions.Research demonstrated that football players possessing a temperament structure that is closely aligned harmonised structure with a high capacity to process stimulation showed higher levels of individual efficacy in attack, defence, and comprehensive effectiveness of performance compared to football players with a harmonised temperament structure but a low capacity to process stimulation.The obtained result emphasises the significance of specific temperament structures in terms of matching the individual's stimulation levels and the their ability to process it.